KEBERMAKNAAN HIDUP PADA IBU RUMAH TANGGA YANG TERINFEKSI HIV&AIDS DARI SUAMINYA - IRIANI INDRI HAPSARI; SITI SAHLAH FAUZIYAH ARIF (Journal of Research and Measurement in Psychology, 2014)
People living with HIV (PLWH) often encounter feelings of shocked, sadness, scared, stress, and disappointed, when they have discovered that they are infected with HIV. If those feelings remain to exist, they may become depressed and even lose their meaning of life. Therefore, the aim of this reseacrh is to find and interpret the meaning of life of a housewife infected with HIV&AIDS from her husband. This research used a qualitative approach with the case study method. The subject is a housewife infected with HIV&AIDS from her husband in which was not involved in any risky acts and behaviours that could transmit HIV to others.The results of this research showed that subject can reach and understand the meaning of life through a few stages. For instance, the stage of tragic event, self-acceptance, finding meaning, realisation of meaning, and meaningful life. The success of these finding is also supported by several components in which this research showed that the component of social support plays very important role for the subject to reach her meaning of life in a great deal. Furthermore, there are three sources of meaning of life. They are creative values, attitudinal values, and experiental values.